2015
DOI: 10.3174/ajnr.a4606
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Treatment and Outcome of Blister-Like Aneurysms

Abstract: BACKGROUND AND PURPOSE:Blister-like aneurysms are uncommon but challenging lesions. Their small size and atypical location often make the diagnosis difficult. Microsurgery and endovascular procedures have been used for their treatment, but there is no consensus on the best treatment technique. We conducted a systematic review and meta-analysis of treatments and outcomes of these vascular lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 10 publications
2
78
0
9
Order By: Relevance
“…33,39 It is also of interest that systematic reviews have shown treatment of blister aneurysms with FDs to result in a higher rate of thromboembolic events compared with non-FD-mediated endovascular treatment, but there was no significant difference in the rate of rebleeding. 44,48 Fur- thermore, although use of FD technology was found to provide a statistically significantly higher rate of mid-to long-term occlusion and a lower rate of retreatment, the difference in the rate of good neurological outcome was not statistically significant between groups.…”
mentioning
confidence: 76%
“…33,39 It is also of interest that systematic reviews have shown treatment of blister aneurysms with FDs to result in a higher rate of thromboembolic events compared with non-FD-mediated endovascular treatment, but there was no significant difference in the rate of rebleeding. 44,48 Fur- thermore, although use of FD technology was found to provide a statistically significantly higher rate of mid-to long-term occlusion and a lower rate of retreatment, the difference in the rate of good neurological outcome was not statistically significant between groups.…”
mentioning
confidence: 76%
“…9 Endovascular procedures included coiling, balloon/stent-assisted coiling, single stent alone, multiple stents, parent artery occlusion, FD alone or with coils. 10 Because of the fragile paper-thin walls of blister aneurysms, surgical clipping met with high rate of intraoperative ruptures which finally led to sacrificing the parent artery. 8,[11][12][13] For the same reason, primary or stent-assisted coiling of blisters carry a high risk of rupture and hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the therapeutic protocol for BBAs of the supraclinoid ICA is rarely mentioned in the literature, and studies more often focus on specific therapeutic methods 5, 6. In fact, treatment of BBAs of the supraclinoid ICA abides by certain principles.…”
Section: Classification and Therapeutic Protocol For Bbasmentioning
confidence: 99%
“…BBAs can grow in many sites, such as the supraclinoid internal carotid artery (ICA), middle cerebral artery, anterior communicating artery, basilar artery, and posterior cerebral artery 3, 4. Among these sites, most BBAs arise from the supraclinoid ICA 5, 6. BBAs of the supraclinoid ICA are distinguished from saccular aneurysms by several unique characteristics, such as a hemispheric and broad-based appearance, a lack of an identifiable neck originating from a nonbranching site of an artery, instability, morphological changes on short-term angiographic follow-up, fragility and the tendency to rupture or regrow 7, 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation